Metabolic response of endurance athletes to training with added load - Rusko, H.; Bosco, C. C. (European Journal of Applied Physiology, 1987)
Endurance athletes were divided into experimental (n = 12) and control (n = 12) groups to investigate the effects of extra-load training on energy metabolism during exercise. A vest weighing 9%-10% body weight was worn every day from morning to evening for 4 weeks including every (n = 6) or every other (n = 6) training session. After 4 weeks the control group had a lower blood lactate concentration during submaximal running, whereas the experimental group had significantly higher blood lactate and oxygen uptake (p less than 0.01--p less than 0.05), and a lower 2 mmol lactate threshold (p less than 0.05) and an increased blood lactate concentration after a short running test to exhaustion (p less than 0.05). Those experimental subjects (n = 6) who used the added load during every training session had a lower 2 mmol lactate threshold, improved running time to exhaustion, improved vertical velocity when running up stairs and an increased VO2 during submaximal running after the added load increased anaerobic metabolism in the leg muscle during submaximal and maximal exercise. An increased recruitment and adaptation of the fast twitch muscle fibres is suggested as the principal explanation for the observed changes.